Mesoporous Silica Nanoparticles: Types, Synthesis, Role in the Treatment of Alzheimer's Disease, and Other Applications - Bhagavathi Sundaram Sivamaruthi; Devesh U. Kapoor; Rajiv R. Kukkar; Mansi Gaur; Gehan M. Elossaily; Bhupendra G. Prajapati; Chaiyavat Chaiyasut (MDPI AG, 2023)
Globally, many individuals struggle with Alzheimer's disease (AD), an unrelenting and incapacitating neurodegenerative condition. Despite notable research endeavors, effective remedies for AD remain constrained, prompting the exploration of innovative therapeutic avenues. Within this context, silica-based nanoplatforms have emerged with pronounced potential due to their unique attributes like expansive surface area, customizable pore dimensions, and compatibility with living systems. These nanoplatforms hold promise as prospective interventions for AD. This assessment provides a comprehensive overview encompassing various forms of mesoporous silica nanoparticles (MSNs), techniques for formulation, and their applications in biomedicine. A significant feature lies in their ability to precisely guide and control the transport of therapeutic agents to the brain, facilitated by the adaptability of these nanoplatforms as drug carriers. Their utility as tools for early detection and monitoring of AD is investigated. Challenges and prospects associated with harnessing MSNs are studied, underscoring the imperative of stringent safety evaluations and optimization of how they interact with the body. Additionally, the incorporation of multifunctional attributes like imaging and targeting components is emphasized to enhance their efficacy within the intricate milieu of AD. As the battle against the profound repercussions of AD persists, MSNs emerge as a promising avenue with the potential to propel the development of viable therapeutic interventions.